Gradient almost Ricci solitons on multiply warped product manifolds - Günsen, S.; Onat, L. (Carpathian Mathematical Publications, 2021)
In this paper, we investigate multiply warped product manifold \[M =B×_b_1 F_1×_b_2 F_2×_b_3 … ×_b_m F_m\] as a gradient almost Ricci soliton. Taking b_i=b for 1≤ i ≤ m lets us to deduce that potential field depends on B. With this idea we also get a rigidity result and show that base is a generalized quasi-Einstein manifold if abla b is conformal.